Development and pilot-testing of an evidence-based quality indicator set for home mechanical ventilation care: the OVER-BEAS project - Martha Schutzmeier; Lilly Sophia Brandstetter; Stephanie Stangl; Jutta Ahnert; Anna Grau; Laura Gerken; Hanna Klingshirn; Bernd Reuschenbach; Tobias Skazel; Maximilian Kippnich; Thomas Wurmb; Peter Heuschmann; et al. (BMC, 2024)
Abstract Background The number of patients depending on home mechanical ventilation (HMV) has increased substantially in Germany in recent years. These patients receive long-term care in different nursing facilities (nursing home, shared living community, private home). However, there are limited data available on the quality of care of HMV patients. The aim of the OVER-BEAS project was to identify quality indicators (QIs) of HMV care using an evidence-based approach. Methods A multidisciplinary board consisting of professionals and experts of HMV provision compiled a set of QIs between March and September 2019. In a structured, transparent process a set of QIs covering structures, processes and outcome of HMV patient's care were proposed and evaluated based on the best available evidence. QIs were defined as relevant, reliable and valid measurements of the quality of HMV care and furthermore to be comprehensive and applicable in practice. Results The experts proposed 40 QIs and consented a final set of 26 QIs. Based on the final set, questionnaires to document the QIs were developed: (1) to assess the quality and describe the structure of the nursing facility; and (2) to gather information on patient-related processes and outcomes. The feasibility of the questionnaires was tested in 5 nursing facilities treating HMV patients. The remarks from the nursing specialists were categorised in three groups: (1) term missing accuracy, (2) problem of understanding, and (3) not documented or documented elsewhere. Mean documentation time by the nursing specialists for one patient was 15 min. Based on this feedback, the questionnaires were finalised. Conclusions We proposed a set of QIs relating to long-term HMV care and developed two questionnaires to collect this information. In a pilot study, we found the set of questionnaires to be feasible in assessing the quality of HMV care according to current evidence. The development of standardised evidence-based QIs to evaluate HMV care is a step towards implementing a standardised quality assurance program to document the quality of care of HMV patients.